PENANGANAN KELUHAN, KELENGKAPAN FASILITAS DAN GOLONGAN LAYANAN PESERTA SEBAGAI FAKTOR PENENTU KEPUASAN PESERTA ASKES SOSIAL PADA PT. ASKES CABANG BANYUMAS DI ASKES CENTER RSU BANYUMAS - Herni Utami Rahmawati; Heri Susilo Widodo (Universitas Amikom Purwokerto, 2011)
The research takes the title of ,.The handling of complaint, completeness of facikty, and the service group of heatth insurence .i-f,n^ ai the main factor of thL health insurance social members in pr. aSKES of Banyumas at health